Independent association of general and central adiposity with risk of gallstone disease: observational and genetic analyses - Zhang, Min; Bai, Ye; Wang, Yutong; Cui, Huijie; Zhang, Wenqiang; Zhang, Li; Yan, Peijing; Tang, Mingshuang; Liu, Yunjie; Jiang, Xia; Zhang, Ben (Frontiers in Endocrinology, 2024)
General obesity is a well-established risk factor for gallstone disease (GSD), but whether central obesity contributes additional independent risk remains controversial. We aimed to comprehensively clarify the effect of body fat distribution on GSD.We first investigated the observational association of central adiposity, characterized by waist-to-hip ratio (WHR), with GSD risk using data from UK Biobank (N=472,050). We then explored the genetic relationship using summary statistics from the largest genome-wide association study of GSD (ncase=43,639, ncontrol=506,798) as well as WHR, with and without adjusting for body mass index (BMI) (WHR: n=697,734; WHRadjBMI: n=694,649).Observational analysis demonstrated an increased risk of GSD with one unit increase in WHR (HR=1.18, 95%CI=1.14-1.21). A positive WHR-GSD genetic correlation ( =0.41, P=1.42×10 -52 ) was observed, driven by yet independent of BMI (WHRadjBMI: =0.19, P=6.89×10 -16 ). Cross-trait meta-analysis identified four novel pleiotropic loci underlying WHR and GSD with biological mechanisms outside of BMI. Mendelian randomization confirmed a robust WHR-GSD causal relationship (OR=1.50, 95%CI=1.35-1.65) which attenuated yet remained significant after adjusting for BMI (OR=1.17, 95%CI=1.09-1.26).Furthermore, observational analysis confirmed a positive association between general obesity and GSD, corroborated by a shared genetic basis ( =0.40, P=2.16×10 -43 ), multiple novel pleiotropic loci (N=11) and a causal relationship (OR=1.67, 95%CI=1.56-1.78).Both observational and genetic analyses consistently provide evidence on an association of central obesity with an increased risk of GSD, independent of general obesity. Our work highlights the need of considering both general and central obesity in the clinical management of GSD.